Quantum drones and the future of military warfare - Sutikno, Tole (International Journal of Informatics and Communication Technology (IJ-ICT), 2023)
The advent of drones has significantly impacted military warfare, providing improved reconnaissance, surveillance, and target acquisition (RSTA), cost savings, increased convenience, safety, and flexibility. A layered network control architecture, known as the internet of drones (IoD), coordinates drone access to controlled airspace and offers navigation services. Various systems, including wireless sensor networks (WSN) and drones directed to an expanded controlling zone, integrate with IoD to improve connection performance. This paper provides an overview of the IoD and the internet of quantum drones (IoQD), highlighting key issues and potential solutions in applications and deployment. The IoQD provides primary features such as secure message exchange, fast communication processes, the viability of creating and deploying private IoQD, and enabling a new field of application, quantum well (QW). In conclusion, the advent of drone technology has significantly improved various aspects of military operations, including reconnaissance, surveillance, and target acquisition. The IoQD offers a promising solution for military networks, facilitating the safe and expedited transfer of data, ultimately benefiting the entire military network.